THE EFFECTIVENESS OF SPATIAL ANALOGIES ON UNDERSTANDING OF NUMBERS IN EARLY CHILDHOOD - Yayang Honora Prabu Sinta; Siti Kamsiyati; Muhammad Munif Syamsuddin (Universitas Sebelas Maret, 2019)
This study aimed to examine the effectiveness of spatial analogies on understanding of numbers in early childhood in TK Islam Salamah and TK Sri Juwita Hanum Surakarta. This study was a quasi-experimental. The design of the study used a non-equivalent design with a sample of 34 children in the experimental group and 35 children in the control group. The technique of collecting data was through performance tests to measure children’s understanding of numbers. The normality test and homogeneity test used kolmogrov smirnov and lavene test of equality of variance. The data analysis used parametric statistics with a significance level p>0.05. The results showed that there was an increase in the mean value in the experimental group and there were significant differences from the control group and the experimental group with a significance value of 0,000. Children can to use the number symbol to count, mention the number symbol from 1 to 10, match numbers with the number symbols, know the concept of less and more numbers also there was an increase in another indicator. It can be concluded that spatial analogies had an effectiveness on the understanding of numbers of children in group B, TK Islam Salamah Surakarta.